2019
DOI: 10.1111/ejn.14323
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in dopaminergic genes predict proactive processes of response inhibition

Abstract: The ability to inhibit a prepared emotional or motor action is difficult but critical to everyday functioning. It is well‐established that response inhibition relies on the dopaminergic system in the basal ganglia. However, response inhibition is often measured imprecisely due to a process which slows our responses and increases subsequent inhibition success known as proactive inhibition. As the role of the dopamine system in proactive inhibition is unclear, we investigated the contribution of dopaminergic gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 182 publications
(236 reference statements)
4
5
0
Order By: Relevance
“…Therefore, designing and validating simpler tasks that minimise these confounds is critical. Indeed, older adults in the Bloemendaal et al study showed a trend towards increased (rather than decreased) proactive slowing in a simple 2-cue condition relative to young adults, a result that mirrors our own finding that older adults show increased PES (Beu, Burns, & Baetu, 2019). So, as it stands, proactive inhibition is likely task-dependent, and may indeed vary in validity across tasks, and perhaps even rely on separate neurochemical equilibrium (e.g., Beu et al, 2019;Rincón-Pérez et al, 2019).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, designing and validating simpler tasks that minimise these confounds is critical. Indeed, older adults in the Bloemendaal et al study showed a trend towards increased (rather than decreased) proactive slowing in a simple 2-cue condition relative to young adults, a result that mirrors our own finding that older adults show increased PES (Beu, Burns, & Baetu, 2019). So, as it stands, proactive inhibition is likely task-dependent, and may indeed vary in validity across tasks, and perhaps even rely on separate neurochemical equilibrium (e.g., Beu et al, 2019;Rincón-Pérez et al, 2019).…”
Section: Introductionsupporting
confidence: 87%
“…To date, there is no adequate formal account of proactive inhibition. However, given the role of proactive inhibition as a strategy to compensate for what may be physiological constraints in achieving optimal reactive inhibition (e.g., Beu, Burns, & Baetu, 2019), it seems likely that it could take two forms in an experimental environment. The first could be considered a predictive form, characterised as attenuating a response pattern under conditions where there is a real or perceived increase in the likelihood of a need to inhibit a response, as in the task modification used by Bloemendaal and colleagues (Bloemendaal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of acute tolerance to impairment in response inhibition was not found in this study, because performance in both the alcohol and placebo group was similar at all time points for all SART measures. Although the observed variance in post−error slowing in the SART appeared high, it was not dissimilar to that found in previous studies (Beu, Burns, & Baetu, 2019). Because the SART did not show any effect of alcohol, there was not sufficient impairment to show recovery as evidence of acute tolerance.…”
Section: Discussionsupporting
confidence: 58%
“…Although the aforementioned studies have informed the role of dopamine in reactive inhibition, the literature concerning dopamine and proactive inhibition remains scarce. D 1 and D 2 gene polymorphisms have been shown to predict engagement of proactive inhibition (measured as post-error slowing in a go/no-go task), such that increased D 1 and decreased D 2 receptor expression are associated with increased proactive inhibition [38]. Given that ropinirole has a relatively high affinity for D 3 receptors, our work extends the mediators of proactive inhibition to include D 3 receptors, as well.…”
Section: A Single Dose Of Ropinirole Reduces/impairs Proactive Inhibimentioning
confidence: 82%